A Incomensurabilidade em Thomas Kuhn e a Educacao Profissional, Cientifica E Tecnologica: Um Ensaio Sobre Interdisciplinaridade e Pratica no Ensino de Tecnologia das Construcoes (Global Journal of Human-Social Science, 2021)
This work aims to demonstrate that the concept of Incommensurability according to Thomas Kuhn originally of the Exact Sciences which explains the change between scientific theories in the Philosophy of Science as well explains on the Technology of buildings in Brazilian built environment from the Colonial period to Contemporary It was observed that the changes in scientific theories have occurred in part with assimilation of previous concepts and part with complete break between paradigms
Keywords: incommensurability; education; philosophy of science; construction technology